Beethoven engraving by Mayer based on Kloeber - Mayer, Carl, 1798-1868 (artist):::Creator::::::::::::; Kloeber, August Karl Friedrich von, 1793-1864 (artist):::Contributor:::::::::::: (Carl Mayer's Kunst-Anstalt; Germany; Nürnberg)
Steel engraving of Beethoven based on chalk portrait by August von Kloeber.